Readability of Literature Supplied with Plant Protection Chemicals (Indian Journal of Extension Education, 2013)
Printed materials have been accepted world wide as an important means of communication and have greater significance in the context of increased literacy level over the last few decades. The effectiveness of these printed materials depends largely on the extent to which they are readable. The present study was undertaken to analyze the readability of literature supplied along with plant protection chemicals. The study was conducted in Sevapuri block of Varanasi district of Uttar Pradesh, because this block has high literacy percentage in comparison to other blocks. Four villages under this block namely Maharajpur, Gaharpur, Jaddupur and Bhelupur were selected randomly for the study. A total of 110 farmers who grew varieties of cereals and vegetables and used Plant Protection Chemicals (PPCs) for protecting their crops from the incidence of insect-pests and diseases were the respondents of the study. The findings of the study revealed that majority of the farmers had completed their higher secondary education (61%). Further all the farmers said that they were aware about literature supplied with PPCs, but only 37 per cent of them read the literature. All the farmers agreed that too many technical words used, font size used, poor paper quality, lack of illustration and difficult to understand the application methods regarding PPCs suggested in the literature considered as main constraints in reading the literature. Hence readability constraints should be eliminated and farmers should be encouraged to read and follow the instructions mentioned in the literature.